(untitled) (SCIENCE TIME JOURNAL, 2026)
The article examines the features of the formation and manifestation of tolerant behavior among university students. Tolerance is considered as an integrative personal quality that includes cognitive, emotional-value and behavioral components. The study analyzes psychological and pedagogical factors influencing the development of tolerant behavior in the university educational environment. Special attention is paid to pedagogical means that contribute to the formation of tolerance in the process of educational interaction.